Assessment of Nature Reserve Park Management for Sustainable Development: Insights from Idanre Hills in Ondo State Southwest, Nigeria - Ademola Adegoroye; Samuel, Ayedogbon Ayodeji; Amos, Olayinka; Olalekan, Oloruntoba Emmanuel (MultiTech Publisher, 2024)
Despite Nigeria is gifted with a wealth of natural resources and rich cultural heritage, is still backward in terms of economic development. Therefore, ecotourism has therefore been identified as a vital regional approach for harmonizing economic growth and conservation. Thus, the study empirically evaluates the current state of ecotourism in Oke Idanre hills in Idanre Local Government Area of Ondo State, Nigeria. Primary and secondary data were collected and sourced with the aid of questionnaire and scheduled Interviews. The data involved qualitative analysis using descriptive statistics. The results revealed that although ecotourism is still at an early stage, some socioeconomic benefits for the Idanre community exist such as the employment of locals as tourist guides and other investments as a result of this destination. The finding shows the use and access of resources by the locals in the Idanre community as logging and poaching have become the order of the day. Locals in a bid to survive the hard-luck of life encroach into protected areas. Also, Idanre locals have had to cope with reduced access to some parts of the hills especially during the day since the site was listed by UNESCO as a world heritage site. The dilapidated site resort has brought about revenue loss to the community. Covid-19 pandemic has brought about a decline in tourist population in Idanre hill; ecotourism has not contributed much revenue towards conservation efforts as not much is generated, bulk still lies on the shoulder of the government who are more interested in oil than tourism. The site offers rich cultural artefacts and a tour guide is usually attached to educate the tourists. Hence this study is necessary to ascertain the current state of ecotourism in Idanre hills looking from the community perspective, the practices, administration, and management of Idanre hills, also recommendations offered are centered on the study of the findings.